Ochrona danych osobowych – obowiązek duszpasterski - Domaszk, Arkadiusz (Prawo Kanoniczne, 2010)
In democratic state the protection of personal data is a legal standard. The basic legal act which is in force in Poland is the Act of 29 August 1997 on the Protection of Personal Data. In the first part of the article there are presented the requirements of polish law related to the above subject. In the second part of the elaboration norms of canon common law, which correspond with subject matter, has been adduced and amplified. In particular, content of 220 Canon of the Code of Canon Law (1983) protects good reputation and privacy of any person. Furthermore norms of the Code include problems connected with ecclesiastical records and safekeeping the documents, which contain personal data. The third part of the article presents norms that oblige to protect personal data within Catholic Church in Poland. Conference of Poland’s Episcopacy in 2009 published an instruction on the protection of personal data. Contemporary law on protection of personal data obliges all database administrators. In that way it also protects Catholics’ and others laws. Adhering to those norms preserve legitimacy of ecclesiastical subject functioning, but also states their pastoral care. Concern for moral good of the faithful includes also respect for every piece of information concerning individual Catholic. New information systems are also the field requiring concern. Polish legal act and ecclesiastical instruction recommends protecting safety of data also in new information systems. That is why ecclesiastical administrators of data ought to protect personal data when using computers, the Internet and all data storage devices. At the same time that subject requires further researches.